CO2 adsorption in Y zeolite: a structural and dynamic view by a novel principal‐component‐analysis‐assisted in situ single‐crystal X‐ray diffraction experiment. Issue 2 (6th February 2019) - Conterosito, Eleonora; Palin, Luca; Caliandro, Rocco; van Beek, Wouter; Chernyshov, Dmitry; Milanesio, Marco
Abstract : In situ single‐crystal X‐ray diffraction data were used to unravel the structural dynamics and enthalpy and entropy of adsorption of CO2 into Y zeolite. A principal‐component‐analysis‐ (PCA) based approach is applied in an innovative way to single‐crystal X‐ray diffraction data analysis, allowing one to selectively detect the information from the subset of active atoms. The potential of and limitations of PCA in single‐crystal diffraction are discussed. Abstract : The increasing efficiency of detectors and brightness of X‐rays in both laboratory and large‐scale facilities allow the collection of full single‐crystal X‐ray data sets within minutes. The analysis of these `crystallographic big data' requires new tools and approaches. To answer these needs, the use of principal component analysis (PCA) is proposed to improve the efficiency and speed of the analysis. Potentialities and limitations of PCA were investigated using single‐crystal X‐ray diffraction (XRD) data collected in situ on Y zeolite, in which CO2, acting as an active species, is thermally adsorbed while cooling from 300 to 200 K. For the first time, thanks to the high sensitivity of single‐crystal XRD, it was possible to determine the sites where CO2 is adsorbed, the increase in their occupancy while the temperature is decreased, and the correlated motion of active species, i.e. CO2, H2 O and Na + . PCA allowed identification and elimination of problematic data sets, and better understanding of the trends of the occupancies of CO2, Na + and water. The quality of the data allowed for the first time calculation of the enthalpy (Δ H ) and entropy (Δ S ) of the CO2 adsorption by applying the van 't Hoff equation to in situ single‐crystal data. The calculation of thermodynamic values was carried out by both traditional and PCA‐based approaches, producing comparable results. The obtained Δ H value is significant and involves systems (CO2 and Y zeolite) with no toxicity, superb stability and chemical inertness. Such features, coupled with the absence of carbonate formation and framework inertness upon adsorption, were demonstrated for the bulk crystal by the single‐crystal experiment, and suggest that the phenomenon can be easily reversed for a large number of cycles, with CO2 released on demand. The main advantages of PCA‐assisted analysis reside in its speed and in the possibility of it being applied directly to raw data, possibly as an `online' data‐quality test during data collection, without any a priori knowledge of the crystal structure.